A Review of Modern Assessment Methods for Metal and Metal-Oxide Based Primers for Substrate Corrosion Protection - McMahon, Matthew E.; Santucci, Raymond J.; Glover, Carol F.; Kannan, Balaji; Walsh, Zachery R.; Scully, John R. (Frontiers in Materials, 2019)
Pigmented coatings developed for the corrosion protection of engineering alloys have been successful in the field of corrosion control, and thus are ubiquitous in application. Supporting this success are an array of methods to diagnostically assess these systems and measure their state of degradation. These methods assist the development of next generation coatings, in-service evaluation, and post-mortem analysis of performance. This review comprehensively explores these modern assessment methods, used to screen candidate corrosion prevention pigments, assess pigment protection efficiency, quantify overall pigment effectiveness, and/or predict coating service lifetime. Coating service life assessment is conducted based on the class of coating considered, as categorized by (1) chemical inhibition, (2) galvanic protection, (3) high impedance ion barrier, or a combination of these protection mechanisms. Exciting new in-situ and operando methods are growing in use to enable high fidelity measurement of chemical inhibitor release and deposition, such as micro and in-situ Raman spectroscopy and inductively coupled plasma atomic emission spectrometry (ICP-AES), to name a few. In the galvanic protection coating class, service life and the state of coating performance are now being quantified through methods such as galvanostatic pulse and accelerated cycle testing. Galvanic throwing power is assessed by scanning vibrating electrode technique (SVET), multi-electrode array (MEA), and scanning kelvin probe (SKP). The performance of high impedance ion barrier coatings has traditionally been understood through use of electrochemical impedance spectroscopy (EIS) and equivalent circuit modeling, which have been applied to all coating classes. Finite element analysis (FEA) models the combined effects of coating resistance, water layer thickness, and pigment potential on galvanic coupling and/or inhibitor species release as well. The development of effective corrosion prevention pigments and the in-service evaluation of their efficiency/effectiveness demands a broad collection of techniques. These methods now include new advances in thermodynamic modeling via chemical stability diagrams to assess pigment function in specific conditions, in-situ pH measurement, as well as energy dispersive (EDS) and x-ray photoelectron spectroscopic (XPS) analyses to determine elemental distribution and corrosion product formation. These techniques and more are explored in this review to document the state-of-the-art in the field.